Genetic variability in brazilian castor (Ricinus communis) germplasm assessed by morphoagronomic traits and gray mold reaction - Neto, Sebastião S. De Oliveira [UNESP]; Zeffa, Douglas M.; Sartori, Maria M.P. [UNESP]; Soares, Dartanhã J.; Zanotto, Maurício D. [UNESP] (FapUNIFESP (SciELO), 2021)
The characterization and conservation of castor accessions in germplasm bank are essential in order to breeding programs achieve its goals. Despite Brazil having the 4th largest castor germplasm bank in the world, castor diversity in Brazil remains little explored. Thus, this study aimed at characterize castor accessions collected in different Brazilian regions by means of 31 morphoagronomic traits and gray mold reaction. Forty accessions of the Universidade do Estado de São Paulo (UNESP), Botucatu, SP, Brazil, germplasm bank were evaluated. Genetic parameters were estimated for the quantitative traits, and the accessions were grouped by Ward method using the standardized Euclidean distance and the simple coincidence index for quantitative and qualitative data, respectively. Qualitative and quantitative traits were important to understand and differentiate castor accessions. The accessions showed a high variation regarding the castor gray mold reaction. The accessions assessed in this study have been preserved and can be used as a source for genetic variability in the development of new castor varieties in breeding programs.
Keywords: Genetic improvement; Genetic variability; Qualitative descriptors; Quantitative descriptors; REML/BLUP